Navigating Self-Efficacy: Coping Strategies of Domestic Migrant Students Facing Homesickness and Insecurity - Nelly Marhayati (Yayasan Darussalam Bengkulu, 2026)
This study aims to explore the emotional experiences, social adjustment, and coping strategies of domestic migrant students in Bengkulu who experience homesickness and insecurity during their adaptation process in higher education. A descriptive qualitative approach was employed, with data collected through semi-structured interviews and observations involving undergraduate students from semesters 2 to 6. The findings indicate that domestic migrant students commonly experience emotional challenges in the early stages of adaptation, including loneliness, anxiety, reduced self-confidence, and feelings of social isolation. These challenges are primarily influenced by environmental transitions, cultural and linguistic differences, and the demands of independent living in a new social context. Despite these difficulties, students gradually develop adaptive coping strategies through peer interaction, social support systems, and both problem-focused and emotion-focused coping mechanisms. The results further show that self-efficacy plays a supportive role in helping students regulate psychological stress, although it is not the sole determining factor in overcoming homesickness. Strong social support networks and effective coping strategies are found to be more dominant in facilitating successful adaptation. Overall, the study highlights the importance of strengthening social support systems and psychological resilience to improve the well-being and adjustment of domestic migrant students in higher education settings.